Biochemical Alterations Associated with Non-Alcoholic Fatty Liver Disease in Iraqi Patients Attending Private Clinics in Baghdad - Omar Tama Al-Akelie; Ammar M. Al-Bayati; Nissrin M. Mustafa; Reyam Abdul Khuder Mohammed (American Journal of Biomedicine and Pharmacy, 2026)
Background: NAFLD is a prevalent metabolic disorder throughout the Middle East; however, the biochemical profile related to NAFLD has not been adequately defined in Iraqi populations. This cross-sectional study provides an overview of liver, metabolic, inflammatory, and oxidative stress biomarkers of NAFLD patients seen in private gastroenterology practices in Baghdad, Iraq. Methods. 120 patients with confirmed NAFLD (diagnosed by abdominal ultrasound based on clinical criteria) and 60 matched healthy control subjects (matched for age and gender) were recruited from March 2023 to September 2024. Fasting serum samples were analyzed for liver function tests (ALT, AST, ALP, GGT, total bilirubin), lipid profile (total cholesterol, triglycerides, LDL and HDL, fasting glucose), insulin resistance (HOMA-IR), complete blood count, C-reactive protein (CRP), ferritin, and malondialdehyde (MDA), and total antioxidant capacity (TAC). Results. Compared to healthy controls, patients with NAFLD had statistically significant higher levels of ALT (62.4 ± 18.3 vs. 22.1 ± 6.4 U/L), AST (48.7 ± 14.9 vs. 19.8 ± 5.7 U/L), GGT (55.3 ± 20.1 vs. 21.4 ± 7.3 U/L), triglycerides (2.31 ± 0.74 vs. 1.12 ±0.31 mmol/L), HOMA-IR (3.87 ± 1.24 vs. 1.43 ± 0.52), CRP (8.6 ± 3.2 vs. 2.1 ± 0.9 mg/L), ferritin (186.4 ± 67.3 vs. 74.2 ± 22.1 μg/L), and MDA (4.18 ± 1.02 vs. 1.76 ± 0.48 nmol/mL) (all p < 0.001). Patients also had significantly lower levels of HDL and TAC. According to multivariate logistic regression analysis, HOMA-IR (OR 4.12, 95% CI 2.34-7.26), MDA (OR 3.67, 95% CI 1.98-6.81), and GGT (OR 2.88, 95% CI 1.54-5.38) were identified as independent predictors of NAFLD severity. Conclusions. Biochemical data support that Iraqi patients with NAFLD have an identifiable biochemical signature indicating hepatocellular injury, atherogenic dyslipidemia, insulin resistance, systemic inflammation, and oxidative stress. These findings propose specialized integrated biochemical screening protocols for Iraqi clinical practices.